Self‐Emergent Protocells Generated in an Aqueous Solution with Binary Macromolecules through Liquid‐Liquid Phase Separation. (11th August 2020) - Sakuta, Hiroki; Fujita, Fumika; Hamada, Tsutomu; Hayashi, Masahito; Takiguchi, Kingo; Tsumoto, Kanta; Yoshikawa, Kenichi
Abstract: Recently, liquid–liquid phase separation (LLPS) has attracted considerable attention among researchers in the life sciences as a plausible mechanism for the generation of microstructures inside cells. LLPS occurs through multiple nonspecific interactions and does not always require a lock‐and‐key interaction with a binary macromolecular solution. The remarkable features of LLPS include the non‐uniform localization and concentration of solutes, resulting in the ability to isolate certain chemical systems and thereby parallelize multiple chemical reactions within the limited space of a living cell. We report that, by using the macromolecules, poly(ethylene glycol) (PEG) and dextran, that exhibit LLPS in an aqueous solution, cell‐sized liposomes are spontaneously formed therein in the presence of phospholipids. In this system, LLPS is generated through the depletion effect of macromolecules. The results showed that cell‐like microdroplets entrapping DNA wrapped by a phospholipid layer emerge in a self‐organized manner. Abstract : Cell‐like microdroplet entrapping DNA wrapped by a lipid layer : Cell‐sized droplets were generated through liquid–liquid phase separation (LLPS) by adapting a PEG/dextran binary solution. They accumulated phospholipids on their surface and entrapped DNA in a self‐organized manner.